PENGGUNAAN CHATGPT DALAM PEMBELAJARAN PAI (PELUANG, TANTANGAN ETIKA, DAN DAMPAKNYA TERHADAP KRITISITAS BERPIKIR SISWA) - Febiola; Unzilawati; Dedy Novriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in Artificial Intelligence (AI) technology, such as ChatGPT, have caused significant disruption in the education sector, including Islamic Religious Education (PAI). This study was conducted to examine the integration of ChatGPT as a learning medium in PAI, map the accompanying ethical challenges, and evaluate its impact on students' critical thinking skills. Employing a Systematic Literature Review (SLR) method with a qualitative approach, this study demonstrates that ChatGPT offers substantial opportunities as an educational virtual assistant that supports personalized learning processes and enriches the exploration of Islamic literature. Conversely, ethical obstacles arise concerning potential plagiarism, information bias, degradation of moral values, and the loss of authenticity in religious reasoning. Unsupervised and unwise utilization also risks diminishing students' critical thinking abilities due to instant dependency syndrome (cognitive offloading). Therefore, a framework for AI literacy based on Islamic values is highly required, alongside transforming the educator's role into a facilitator and moral guide, and cultivating reflective prompt engineering skills.